RBL cells as models for in vitro studies of mast cells and basophils. Issue 1 (12th February 2018) - Falcone, Franco H.; Wan, Daniel; Barwary, Nafal; Sagi‐Eisenberg, Ronit
Summary: Since their establishment in 1981, RBL‐2H3 cells have been widely used as a mast cell (MC) model. Their ability to be easily grown in culture in large amounts, their responsiveness to FcεRI‐mediated triggers and the fact that they can be genetically manipulated, have provided advantages over primary MCs, in particular for molecular studies relying on genetic screening. Furthermore, the ability to generate clones that stably express proteins of interest, for example, a human receptor, have marked the RBL cells as an attractive MC model for drug screening. Indeed, 3 RBL reporter cell lines (RS‐ATL8, NFAT‐DsRed, and NPY‐mRFP) have been generated providing useful models for drug and allergen screening. Similarly, RBL cells stably expressing the human MrgprX2 receptor provide a unique paradigm for analyzing ligand interactions and signaling pathways of the unique human receptor. Finally, transient co‐transfections of RBL cells allow functional genomic analyses of MC secretion by combining library screening with simultaneous expression of a reporter for exocytosis. RBL cells thus comprise powerful tools for the study of intracellular membrane trafficking and exocytosis and the detection of allergens, vaccine safety studies and diagnosis of allergic sensitization. Their recent uses as an investigative tool are reviewed here.